The Effect of Performance Incentives on Employee Efficiency in Durkhill Microfinance Company Limited - Brenda Alumo (Uganda Christian University, 2023)
This study sought to establish the Effect of Performance Incentives on Employee Efficiency in Durkhill Micro Finance Company limited. The main objective of the study is to investigate the effects of incentives on the efficiency of employees. The following were the objectives of the study: to determine whether micro finance institutions encourage employee efficiency through incentives, to determine the effect of financial incentives on employees and evaluate the effect of non-financial performance incentives on employees. To achieve these goals, a questionnaire was designed based on the intended objectives. Chapter two looked at performance incentives, financial performance incentives, non- financial performance incentives and employee efficiency, conceptual framework, review of empirical studies and theoretical reviews. Chapter three presented the procedures to be employed for the collection and analysis of the data relevant to the investigation. These included: research design, population of the study, sample size and sampling technique, source of data, methods of data collection and method of data analysis. Chapter four presented the completed questionnaires were then analyzed and processed. The findings of the study reveal that there is a positive relationship between incentives and efficiency. Establishments are encouraged to look at issues that not only promote monetary incentives. They are encouraged to involve employees in processes that are aimed at attaining organizational effectiveness.
This is a dissertation.